Facile hydrogenation of N-heteroarenes by magnetic nanoparticle-supported sub-nanometric Rh catalysts in aqueous medium. Issue 18 (24th August 2018) - Nasiruzzaman Shaikh, M.; Aziz, Md. Abdul; Kalanthoden, Abdul Nasar; Helal, Aasif; Hakeem, Abbas S.; Bououdina, Mohamed
Abstract : This work describes the preparation and systematic characterization of a reusable magnetic heterogeneous nanocatalyst (Rh@Fe3 O4 ) for the hydrogenation of N-heterocycles and simple aromatics. Abstract : The hydrogenation of nitrogen-containing heterocyclic precursors in aqueous medium at low temperature without imposing molecular hydrogen pressure is quite challenging. Herein, we report the synthesis and performance of a novel catalyst capable of facile hydrogenation (employing tetrahydroxydiboron (THDB) as the reductant) of N-heteroarenes in water at 80 °C with good recyclability. Rhodium particles in the sub-nano range (<1 nm) were produced by in situ reduction of a Rh precursor on freshly prepared superparamagnetic iron oxide nanoparticles (SPIONs, Fe3 O4 ), using aqueous ammonia as a reducing agent at 50 °C. HRTEM and elemental mapping images reveal a homogeneous distribution of <1 nm Rh particles within the matrix of Fe3 O4 nanoparticles having an average size within a narrow range of 7–9 nm. The superparamagnetic nature of the composite was confirmed by VSM analysis. The Rh@Fe3 O4 catalyst was found to be highly efficient in the heterogeneous hydrogenation of nitrogen-containing heterocyclic compounds with quantitative conversion. It showed selectivity towards the hydrogenation of 1, 2, 3, 4-tetrahydroquinoline (py-THQ) in water using THDB with a high TOF of 1632 h −1 . These results are compared with the conversion and selectivity data obtained from reduction with molecular hydrogen gas pressure. The catalytic activity is extended to the successful hydrogenation of simple aromatics like benzene, toluene etc. Isotopic labelling studies were performed to determine the source of hydrogen in quinoline hydrogenation in the presence of THDB. It was found that it could be used for 16 consecutive cycles with gaseous hydrogen, without any undesired by-products; it also retained its original crystallinity.